The Filipino ballet examining process of indigenization and its identification in/of nation - Jacinto, Joelle Florence Patrice Banzon
This dissertation examines the Filipinization of ballet, that is the processes of indigenization and localization of a foreign art form into an undeniable part of Philippine culture. It analyzes key Filipino ballets to determine what about the Filipino and Filipino culture are their choreographers trying to present or represent, and why these are important to perform, whether for international audiences or for other Filipinos. This analysis is framed within existing discussions of Filipinization, particularly the indigenizing of cultural elements, theoretical perspectives and modes of thought, as articulated by Virgilio Enriquez, Prospero Covar, and F. Landa Jocano, and their, along with Resil Mojares’ separate yet similar concepts of diwa as a shared national soul. The Filipino ballets that will be discussed in this paper are choreographed by seven of the most prominent ballet choreographers in the Philippines: Felicitas Radaic, Basilio Esteban Villaruz, Tony Fabella, Gener Caringal, Eli Jacinto, Agnes Locsin, and Ronilo Jaynario.